Mutations in the translocon‐associated protein complex subunit SSR3 cause a novel congenital disorder of glycosylation. Issue 5 (16th April 2019) - Ng, Bobby G.; Lourenço, Charles M.; Losfeld, Marie‐Estelle; Buckingham, Kati J.; Kircher, Martin; Nickerson, Deborah A.; Shendure, Jay; Bamshad, Michael J.; ,; Freeze, Hudson H.
Abstract: The translocon‐associated protein (TRAP) complex facilitates the translocation of proteins across the endoplasmic reticulum membrane and associates with the oligosaccharyl transferase (OST) complex to maintain proper glycosylation of nascent polypeptides. Pathogenic variants in either complex cause a group of rare genetic disorders termed, congenital disorders of glycosylation (CDG). We report an individual who presented with severe intellectual and developmental disabilities and sensorineural deafness with an unsolved type I CDG, and sought to identify the underlying genetic basis. Exome sequencing identified a novel homozygous variant c.278_281delAGGA [p.Glu93Valfs*7] in the signal sequence receptor 3 ( SSR3 ) subunit of the TRAP complex. Biochemical studies in patient fibroblasts showed the variant destabilized the TRAP complex with a complete loss of SSR3 protein and partial loss of SSR1 and SSR4. Importantly, all subunit levels were corrected by expression of wild‐type SSR3. Abnormal glycosylation status in fibroblasts was confirmed using two markers proteins, GP130 and ICAM1. Our findings confirm mutations in SSR3 cause a novel CDG. A novel frameshift variant in the translocon associated protein, SSR3, disrupts the stability of the TRAP complex and causes a novel Congenital Disorder of Glycosylation.